World economy on the down-track - Günter Großer; Günter Weinert (Intereconomics, 1981)
1979 saw a pronounced cyclical downturn with mounting, inflation and balance of payments problems bear upon the western industrialized countries with the long-expected recession materializing in the USA early in 1980. In Western Europe demand and production began to slide a little later. Increasing signs of a nascent downtrend were also to be seen in Japan. What are the prospects for the current year?
Keywords: 330; Economic Trends